2018
DOI: 10.1038/s41598-018-32111-z
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth-promoting rhizobacteria promote plant size inequality

Abstract: The uniformity of crop yield is extremely important for consumers and of as much relevance to the grower as overall yield. However, size inequality within a plant population is rarely measured and has never before been considered in relation to the use of beneficial microbes for yield enhancement. For the first time, we show that addition of soil bacteria to calabrese plants significantly increased size inequality. These effects were usually more apparent in above-ground biomass. This was caused by some (but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 31 publications
(45 reference statements)
2
26
0
2
Order By: Relevance
“…In all the stress conditions the mean root length for all genotypes varied from 12.72 cm (line 404) to 14.10 cm (Sakha93). Previous studies have shown the ability of PGPR had to generate IAA has been related to improve wheat growth under saline conditions [48] , [49] and it is similar to previous data was recorded by several workers who confirmed that inoculation with PGPR (Pseudomonas and Bacillus) to wheat improved plant production, yield, and physiological attributes [50] , [51] . Our results agreement with [52] , [53] who found that Bacteria containing ACC deaminase activity would act to reduce the level of stress ethylene and thus could resistance to various stresses and insignificant improvement in plant growth characters was observed in Ps.…”
Section: Resultssupporting
confidence: 86%
“…In all the stress conditions the mean root length for all genotypes varied from 12.72 cm (line 404) to 14.10 cm (Sakha93). Previous studies have shown the ability of PGPR had to generate IAA has been related to improve wheat growth under saline conditions [48] , [49] and it is similar to previous data was recorded by several workers who confirmed that inoculation with PGPR (Pseudomonas and Bacillus) to wheat improved plant production, yield, and physiological attributes [50] , [51] . Our results agreement with [52] , [53] who found that Bacteria containing ACC deaminase activity would act to reduce the level of stress ethylene and thus could resistance to various stresses and insignificant improvement in plant growth characters was observed in Ps.…”
Section: Resultssupporting
confidence: 86%
“…The beneficial effects of B. thuringiensis on plants are due to direct and indirect mechanisms, including nitrogen fixation, siderophore production, plant nutrient solubilization, and plant growth hormone production [12][13][14]. However, the plant responses are often variable due to inconsistent performance of inoculants under field conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of inoculants to survive in the soil is an important factor for their ability to function under field conditions [15,16]. Hence, quantification of inoculants in the soil is helpful to determine the success of PGPR under field conditions [1,6,17].…”
Section: Introductionmentioning
confidence: 99%
“…These results have important implications for consumers as well as for farmers, growers, and producers of microbial inoculants. It has been suggested that in future studies of organic systems, an analysis of size inequality should accompany experiments involving PGPR because these products need to be more made-to-order to specific crop situations or soil types, and a universal inoculant is therefore unlikely to be developed at present (Gange & Gadhave, 2018).…”
Section: Plant Productivitymentioning
confidence: 99%